Studi Komparatif terhadap Implikasi Kenosis dalam Filipi 2:7 dan Jalan Menuju Pengosongan Diri dalam Buddhisme - Mordekai Mordekai (Melo: Jurnal Studi Agama-agama, 2022)
Kenosis is a concept that was born based on Paul's narrative in Philippians 2:7 about "emptying oneself". In theory, it is emphasized that Jesus has taken on His human nature. But He in His incarnation by no means gave up His divine nature. Even in that context, He Himself had become a real man. The purpose of this study is to describe the kenosis of Jesus Christ in Philippians 2:7 and self-emptying in spiritual Buddhism, as an effort to find differences or similarities. The method used in this study is comparative, namely by comparing the concept of kenosis in Philippians 2:7 and self-emptying in Buddhism. Kenosis is God's act of emptying himself by becoming human. Such a path is taken by Allah, as an alternative in realizing His mission of saving the world. whereas self-emptying in Buddhism is an act of detachment from attachment to matter and all that is temporary. Self-emptying in Buddhism is known as voidness. Self-emptying is a way of freeing oneself from suffering by focusing on the divine. The kenosis of Jesus Christ and self-emptying in Buddhism meet in the pursuit of truth. Kenosis is God's attempt to reconcile Himself with the world including justifying human beings, while self-emptying in Buddhism justification is carried out by humans themselves. Buddhists empty themselves in order to attain sainthood by standing on the divine.